A Highly Sensitive Electrochemical Sensing Platform Based on P-doped Fe/Fe3O4@C for the Detection of 4-Nitrophenol. Issue 9 (1st September 2022) - Ren, Dongmei; Wang, Xingwen; Leng, Chunpeng; Meng, Wei; Zhang, Jingrui; Han, Chao
Abstract : 4-Nitrophenol (4-NP) is a typical organic pollutant, thus it is urgent to detect it in environmental samples. This study rationally designed a novel electrode material of P-doping Fe/Fe3 O4 @C (P-Fe/Fe3 O4 @C) prepared with MIL-88 as precursor. P2h -Fe/Fe3 O4 @C-700 was synthesized by calcining MIL-88 at 700 °C, followed by annealing process with NaH2 PO2 for 2 h. The P2h -Fe/Fe3 O4 @C-700 modified glassy carbon electrode (P2h -Fe/Fe3 O4 @C-700/GCE) showed a high electrocatalytic activity toward 4-NP reduction due to its active metal center, fine-tuned electronic structure by P-doping, as well as good electrical conductivity. It exhibited excellent sensing behaviors in 4-NP detection with rather high sensitivities of 1415.43 μ A·mM −1 ·cm −2 and 424.63 μ A·mM −1 ·cm −2 in the 4-NP concentration of 5 to 100 μ M and 100 to 1200 μ M, respectively, with a low detection limit of 0.462 μ M. The P2h -Fe/Fe3 O4 @C-700/GCE still had good selectivity for 4-NP detection in the presence of common interferences. In addition, it was found that the current response towards 4-NP at P2h -Fe/Fe3 O4 @C-700/GCE retained more than 97% of its initial value after one week, indicating a good long-term stability. Furthermore, the P2h -Fe/Fe3 O4 @C-700/GCE exhibited a good reproducibility. The constructed P2h -Fe/Fe3 O4 @C-700/GCE achieved practical uses for the sensing of 4-NP in tap water with satisfactory recoveries.